PERENCANAAN TENAGA KERJA DAERAH KOTA PADANG 2014-2018 - Mr Sofyardi (Universitas Negeri Medan, 2017)
With the ever-increasing number of people and the labor force on the one hand, and the limited employment opportunities on the other hand have resulted in an imbalance between supply and labor demand. If this problem is not resolved successfully, it can have adverse impacts in the social, economic, political, and security fields. The handling of employment issues can only be successful if based on good manpower planning. Therefore, the immediate problem faced is how to find the right balance between the growth of the labor force and the employment opportunities in the development process. It is therefore necessary to projection the provision of manpower in relation to the business of creating employment opportunities in the future